2016
DOI: 10.1097/dcr.0000000000000512
|View full text |Cite
|
Sign up to set email alerts
|

Patients Prefer Propofol to Midazolam Plus Fentanyl for Sedation for Colonoscopy

Abstract: The use of propofol for conscious sedation during colonoscopy is associated with greater patient satisfaction and less pain when compared with midazolam/fentanyl, as perceived by the patient and endoscopist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 13 publications
3
15
0
Order By: Relevance
“…They occurred in 5.3% of cases and were mild in nature. These results are comparable with others, placing their frequency at 4.4 to 26% (11,22,23). The reason percentages vary depends mainly on whether low blood pressure, either symptomatic or not, is included or not among the side effects.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…They occurred in 5.3% of cases and were mild in nature. These results are comparable with others, placing their frequency at 4.4 to 26% (11,22,23). The reason percentages vary depends mainly on whether low blood pressure, either symptomatic or not, is included or not among the side effects.…”
Section: Discussionsupporting
confidence: 88%
“…This was perhaps caused by initiating sedation with lower doses of midazolam and meperidine (26). The cecum was successfully reached in 86.7% of the cases, which is comparable to other studies (23,26). When the cases in which the exploration could not be completed for reasons unrelated to sedation were excluded, this figure exceeded 90%, complying with the minimum standard recommended by the ESGE (27).…”
Section: Discussionsupporting
confidence: 83%
“…We performed full-text reviews of 333 articles and identified 9 studies that met all inclusion criteria. [18][19][20][21][22][23][24][25][26] Because our original search was designed to be inclusive of studies of both upper and lower endoscopy and any sedative used, the most frequent reasons for exclusion at the full-text stage were for studies of only upper/advanced endoscopic procedures (n Z 181) or studies that did not compare propofol (AE short-acting opioids) with midazolam (AE short-acting opioids) (n Z 104).…”
Section: Study Selectionmentioning
confidence: 99%
“…Sedation can suppress patient consciousness and cause anterograde amnesia during endoscopy as well as decrease patient anxiety and pain at the time of examination [ 1 ]. This improves patient satisfaction with endoscopy and increases their willingness to undergo the next examination [ 2 , 3 ]. However, unintentional deep sedation can lead to various complications, including hypoxia, hypotension, and arrhythmia [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%